Rationale, design and methods planned in a prospective study concerning the circadian rhythm of heart rate asymmetry in healthy subjects - Sibrecht, Greta; Krauze, Tomasz; Dobkowska, Renata; Wykrętowicz, Andrzej; Piskorski, Jarosław; Guzik, Przemysław (Journal of Medical Science, 2020)
Heart rate asymmetry (HRA) is a physiological phenomenon caused by an unequal (asymmetric) contribution of heart rate decelerations and accelerations to the variability (variance) and microstructure of the heart rhythm of sinus origin. HRA has been studied in healthy people and patients with heart failure, diabetes, obstructive sleep apnoea, ischaemic heart disease, and survivors of myocardial infarction. HRA is a particular form of the heart rate variability (HRV) phenomenon related to the changes in the duration of cardiac cycles of sinus origin. HRV is influenced by physical activity, age, gender or time of day. It has been reported that HRA expression differs between day and night. However, its circadian rhythm has not been analysed so far. Moreover, the differences in HRA expression related to gender, level of physical activity or age have not been investigated either. With this study, we aim to explore the circadian rhythm of the HRA features, as well as the relation of the HRA expression to gender, physical activity, sleep pattern and body composition in a group of at least 100 healthy adults of both sexes aged between 19 and 60. This study might provide reference values for HRA as well as confirming or dismissing the existence of circadian rhythm of this physiological phenomenon.
Keywords: ageing; cardiovascular time series; circadian rhythm; heart rate asymmetry; heart rate variability; physical activity; sex differences